Personality predictors of exercise addiction in competitive sport - Vítková, T.; Rusnáková, K.; Mudrák, J. (Journal of Sports Sciences, 2025)
Exercise addiction is increasingly recognized as a possible threat to athletes` well-being, especially in elite sports. However, research on underlying personality predictors predisposing athletes to exercise addiction remains limited. This study hypothesized several key personality attributes including athletic identity, sport motivation, perfectionism, and neuroticism as possible risk factors of exercise addiction in elite athletes and examined relationships between these personality attributes and symptoms of exercise addiction in 168 Czech elite athletes aged from 18 to 30 years. Results showed that 16.5% of athletes exhibited signs of exercise addiction, while 76.7% were at risk with low symptom severity. Multiple linear regression indicated that neuroticism, introjected regulation, and athletic identity significantly predicted exercise addiction (F(3, 164) = 32.63, p < .001, R2 = .36). These findings underscore the importance of psychological factors in understanding exercise addiction among athletes. The high prevalence suggests discrepancies in diagnosing exercise addiction and inconsistent use of diagnostic tools, necessitating cautious interpretation of the results.